Determinan customer satisfaction dan customer loyalty pada klinik kandungan - Ariyanti, Nevi Chania Dwi (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2021)
This study aims to examine and analyze the effect of Physical Evidence, Trust, and E-Service Quality on Customer Loyalty through Customer Satisfaction. In this study using a quantitative approach, because research data in the form of number and analysis using statistics. Data analysis techniques to answer hypothese using path analysis. The results showed that: (1) Physical Evidence had a significant effect on Customer Satisfaction, (2) Trust had a significant effect on Customer Satisfaction, (3) E-Service Quality had a significant effect on Customer Satisfaction, (4) Physical Evidence had a significant effect on Customer Loyalty, (5) Trust has no significant effect on Customer Loyalty, (6) E-Service Quality has no significant effect on Customer Loyalty, (7) Customer Satisfaction had a significant effect on Customer Loyalty.